Breaking Barriers: Inclusive Brand Awareness on KamiBijak’s Instagram - Dionisius Ratsongko; Silvanus Alvin (Dinasti International Journal of Management Science, 2023)
This research article explores social media marketing's role in enhancing brand awareness and promoting disability inclusivity through the case study of KamiBijak, an Indonesian disability-focused media platform. The study addresses challenges faced by individuals with disabilities in accessing resources and meaningful employment, hindering progress towards Sustainable Development Goals (SDGs). KamiBijak stands out as the first platform catering to individuals with disabilities, particularly the deaf community.Using a qualitative research design, the study includes interviews with key informants, including individuals with disabilities involved in content creation. Findings show that KamiBijak predominantly uses videos and infographics on Instagram, effectively meeting diverse audience needs. The platform's commitment to accessible content featuring sign language and engaging with the audience fosters a sense of community and strengthens brand awareness. The research highlights Instagram's significance as a powerful marketing tool and underscores KamiBijak's inclusive content strategy's effectiveness. KamiBijak's employment of individuals with disabilities showcases dedication to empowering the community. The study emphasizes media representation and social media marketing's role in driving social change and sustainable development. Further exploration into audience perceptions and experiences with KamiBijak could enhance understanding of its impact on disability inclusivity and advocacy.